7 Venous Congestion as Measured by Echocardiography Predicts Severity of Renal Dysfunction and Survival in Patients with Heart Failure. (3rd June 2016) - Singh, Jagdeep; Muhammad Iqbal, AH; Soujeri, Bayan; Levin, Daniel; Lang, Chim C
Abstract : Introduction: Renal dysfunction in patients with heart failure (HF) has traditionally been attributed to poor cardiac output. There is currently a growing body of evidence to suggest that renal venous congestion (VC) plays a more important role than hypo-perfusion. However, a vast majority of them have been invasive studies measuring pulmonary artery and central venous pressures as markers of venous congestion. We, therefore, aimed to determine if VC as determined by inferior vena cava (IVC) dilatation using echocardiography was associated with worsening renal function, HF hospitalisation and all-cause mortality. Methods: We designed a population-based, longitudinal cohort study of 1034 unselected (acute/chronic) HF patients. All patients were symptomatic and required the use of loop diuretic therapy. VC was defined as IVC diameter >2.1 cm as determined by echocardiography performed nearest to the time of recruitment into study. Renal function was determined by estimated glomerular filtration rate (eGFR) using the abbreviated MDRD equation. Logistic regression models were used to examine the association between VC and eGFR. Cox proportional hazard models were applied to examine the influence of VC on all-cause mortality and CHF hospitalisations. Results: Logistic regression models showed that those with severe renal impairment (eGFR<30) were more likely to have VC compared to those with an eGFR >60 (Odds Ratio=7.7; 95% CI(1.6–10.5), p = 0.012). Multivariate analysis showed that those with VC had significantly worse survival than those without VC after adjusting for age, sex, eGFR and furosemide daily dose (hazard ratio [HR]: 1.6, 95% CI: 1.15–1.96; p = 0.002). There was also a nonsignificant trend towards shorter time to first hospitalisation for HF in the VC group compared to those without VC (hazard ratio [HR]: 1.22, 95% CI: 0.96–1.56; p = 0.103). Conclusions: VC as determined by dilated IVC on echocardiography is associated with worsening renal function in an unselected group of HF patients. This readily available and non-invasive test can also be used to predict HF hospitalisation and all-cause death in this patient group.